Semiconductor Device
A film-like adhesive with a controlled inorganic filler content addresses copper ion permeation and adhesive strength issues, enhancing semiconductor device reliability by suppressing ion migration and maintaining robust adhesion.
Patent Information
- Application Number
- JP2023181011
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-26
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2039-09-24
AI Technical Summary
Conventional adhesives used in semiconductor packages fail to sufficiently suppress copper ion permeation and maintain adequate adhesive strength, leading to electrical signal loss and malfunctions.
A film-like adhesive comprising a specific range of inorganic filler content (0.5 to 10 parts by mass) in a formulation with a thermosetting resin, curing agent, and acrylic rubber, which suppresses copper ion permeation while maintaining excellent adhesive strength.
The adhesive effectively prevents copper ion permeation and ensures strong adhesion, reducing electrical defects in semiconductor devices.
Smart Images

Figure 0007655362000007 
Figure 0007655362000008 
Figure 0007655362000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a film-like adhesive, an adhesive sheet, a semiconductor device, and a method for manufacturing the same. [Background technology]
[0002] In recent years, stacked MCPs (Multi Chip Packages), in which semiconductor elements (semiconductor chips) are stacked in multiple layers, have become widespread and are used as memory semiconductor packages for mobile phones and mobile audio devices. In addition, as mobile phones and other devices become more multifunctional, semiconductor packages are being made faster, more dense, and more integrated. Accordingly, copper is being used as a wiring material for semiconductor chip circuits to increase speed. Also, from the perspective of improving the reliability of connections to complex mounting boards and promoting heat dissipation from semiconductor packages, lead frames made of copper are beginning to be used.
[0003] However, copper is prone to corrosion, and in order to reduce costs, there is a trend toward simplifying the coating materials used to ensure the insulation of the circuit surface, making it difficult to ensure the electrical properties of the semiconductor package. In particular, in semiconductor packages in which semiconductor chips are stacked in multiple stages, copper ions generated by corrosion tend to move inside the adhesive, causing electrical signal loss within the semiconductor chip or between the semiconductor chips.
[0004] In addition, from the viewpoint of high performance, semiconductor elements are often connected to complex mounting boards, and there is a tendency to prefer lead frames made of copper to improve connection reliability. Even in such cases, copper ions generated from the lead frame can cause problems with loss of electrical signals.
[0005] Furthermore, in semiconductor packages that use copper-based components, there is a high possibility that copper ions will be generated from the components, causing electrical malfunctions, and sufficient HAST resistance may not be achieved.
[0006] From the viewpoint of preventing loss of electrical signals, etc., adhesives that capture copper ions generated within semiconductor packages have been studied. For example, Patent Document 1 discloses an adhesive sheet for manufacturing semiconductor devices, which comprises a thermoplastic resin having an epoxy group and no carboxyl group, and an organic complex-forming compound that has a heterocyclic compound containing a tertiary nitrogen atom in the ring atom and forms a complex with a cation.
[0007] However, conventional adhesives are not sufficient in terms of suppressing copper ion permeation through the adhesive and in terms of adhesive strength, and there is still room for improvement. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2013-026566 A Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, a main object of the present invention is to provide a film-like adhesive that sufficiently suppresses copper ion permeation into the adhesive while also exhibiting excellent adhesive strength. [Means for solving the problem]
[0010] After extensive research, the inventors discovered that by adjusting the content of inorganic filler in the film adhesive to a specific range, it is possible to sufficiently suppress copper ion permeation within the adhesive while also achieving excellent adhesive strength, and thus completed the present invention.
[0011] One aspect of the present invention provides a film-like adhesive for bonding a semiconductor element and a support member on which the semiconductor element is mounted, the film-like adhesive containing a thermosetting resin, a curing agent, an acrylic rubber, and an inorganic filler, the content of the inorganic filler being 0.5 to 10 parts by mass per 100 parts by mass of the total mass of the thermosetting resin, the curing agent, the acrylic rubber, and the inorganic filler, and the film-like adhesive having a thickness of 15 μm or less.
[0012] The content of the inorganic filler is 0.5 to 10 parts by mass relative to 100 parts by mass of the total mass of the thermosetting resin, the curing agent, the acrylic rubber, and the inorganic filler. When the content of the inorganic filler is 0.5 parts by mass or more, the adhesive strength, wafer adhesion, elastic modulus, and bulk strength of the film-like adhesive tend to be excellent. When the content of the inorganic filler is 10 parts by mass or less, copper ion permeation in the adhesive is sufficiently suppressed, and the appearance and embeddability of the coated surface tend to be excellent.
[0013] In another aspect, the present invention provides an adhesive sheet comprising a substrate and the above-mentioned film-like adhesive provided on one surface of the substrate. The substrate may be a dicing tape.
[0014] In another aspect, the present invention provides a semiconductor device comprising a semiconductor element, a support member on which the semiconductor element is mounted, and an adhesive member provided between the semiconductor element and the support member and adhering the semiconductor element and the support member, the adhesive member being a cured product of the film-like adhesive described above. The support member may include a member made of copper.
[0015] In another aspect, the present invention provides a method for manufacturing a semiconductor device, comprising a step of adhering a semiconductor element to a support member using the above-mentioned film-like adhesive.
[0016] In another aspect, the present invention provides a method for manufacturing a semiconductor device, comprising the steps of: attaching the film-like adhesive of the adhesive sheet to a semiconductor wafer; cutting the semiconductor wafer to which the film-like adhesive has been attached, thereby producing a plurality of individual semiconductor elements with the film-like adhesive; and adhering the semiconductor elements with the film-like adhesive to a support member. The method for manufacturing a semiconductor device may further comprise a heating step using a reflow furnace. Effect of the Invention
[0017] According to the present invention, a film-like adhesive that sufficiently suppresses copper ion permeation into the adhesive and has excellent adhesive strength is provided. Also, according to the present invention, an adhesive sheet and a semiconductor device using such a film-like adhesive are provided. Furthermore, according to the present invention, a method for manufacturing a semiconductor device using the film-like adhesive or the adhesive sheet is provided. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a film-like adhesive. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing one embodiment of an adhesive sheet. [Diagram 3] FIG. 4 is a schematic cross-sectional view showing another embodiment of the adhesive sheet. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another embodiment of the adhesive sheet. [Diagram 5] FIG. 4 is a schematic cross-sectional view showing another embodiment of the adhesive sheet. [Figure 6] 1 is a schematic cross-sectional view showing an embodiment of a semiconductor device; [Figure 7] FIG. 11 is a schematic cross-sectional view showing another embodiment of a semiconductor device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiment. In the following embodiment, the components (including steps, etc.) are not essential unless specifically stated. The size of the components in each figure is conceptual, and the relative relationship of the size between the components is not limited to that shown in each figure.
[0020] The same applies to the numerical values and their ranges in this specification, and the present invention is not limited thereto. In this specification, the numerical range indicated using "~" indicates a range including the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit described in one numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples.
[0021] In this specification, (meth)acrylate means acrylate or the corresponding methacrylate, and the same applies to other similar expressions such as (meth)acryloyl group, (meth)acrylic copolymer, etc.
[0022] The film-like adhesive according to one embodiment is a film-like adhesive for bonding a semiconductor element and a support member on which the semiconductor element is mounted, the film-like adhesive containing (A) a thermosetting resin, (B) a curing agent, (C) an acrylic rubber, and (D) an inorganic filler, the content of the inorganic filler being 0.5 to 10 parts by mass per 100 parts by mass of the total mass of the thermosetting resin, the curing agent, the acrylic rubber, and the inorganic filler, and the thickness of the film-like adhesive being 15 μm or less.
[0023] The film-like adhesive can be obtained by forming an adhesive composition containing (A) a thermosetting resin, (B) a curing agent, (C) an acrylic rubber, and (D) an inorganic filler into a film. The film-like adhesive and adhesive composition may be capable of going through a semi-cured (B stage) state and then becoming fully cured (C stage) after a curing treatment.
[0024] (A) Component: Thermosetting resin From the viewpoint of adhesiveness, the (A) component may be an epoxy resin. Any epoxy resin having an epoxy group in the molecule may be used without particular limitation. Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, stilbene type epoxy resins, triazine skeleton-containing epoxy resins, fluorene skeleton-containing epoxy resins, triphenol methane type epoxy resins, biphenyl type epoxy resins, xylylene type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene type epoxy resins, polyfunctional phenols, and diglycidyl ether compounds of polycyclic aromatics such as anthracene. These may be used alone or in combination of two or more. Among these, the (A) component may be a cresol novolac type epoxy resin, a bisphenol F type epoxy resin, or a bisphenol A type epoxy resin from the viewpoint of film tackiness, flexibility, and the like.
[0025] The epoxy equivalent of the epoxy resin is not particularly limited, but may be 90 to 300 g / eq, 110 to 290 g / eq, or 110 to 290 g / eq. When the epoxy equivalent of the epoxy resin is within such a range, the film adhesive tends to have sufficient flowability while maintaining the bulk strength.
[0026] (B) Component: Hardener The component (B) may be a phenolic resin that can be a curing agent for epoxy resins. Any phenolic resin can be used without particular limitation as long as it has a phenolic hydroxyl group in the molecule. Examples of the phenolic resin include novolac-type phenolic resins obtained by condensing or co-condensing phenols such as phenol, cresol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol and / or naphthols such as α-naphthol, β-naphthol, and dihydroxynaphthalene with a compound having an aldehyde group such as formaldehyde under an acidic catalyst, allylated bisphenol A, allylated bisphenol F, allylated naphthalenediol, phenol novolac, and phenol aralkyl resins and naphthol aralkyl resins synthesized from phenols such as phenol and / or naphthols and dimethoxyparaxylene or bis(methoxymethyl)biphenyl. These may be used alone or in combination of two or more. Among these, the phenolic resin may be a phenol aralkyl resin or a naphthol aralkyl resin.
[0027] The hydroxyl equivalent of the phenol resin may be 70 g / eq or more, or 70 to 300 g / eq. When the hydroxyl equivalent of the phenol resin is 70 g / eq or more, the storage modulus of the film tends to be improved, and when it is 300 g / eq or less, defects due to the generation of foaming, outgassing, etc. can be prevented.
[0028] The ratio of the epoxy equivalent of the epoxy resin to the hydroxyl equivalent of the phenol resin (epoxy equivalent of the epoxy resin / hydroxyl equivalent of the phenol resin) may be 0.30 / 0.70 to 0.70 / 0.30, 0.35 / 0.65 to 0.65 / 0.35, 0.40 / 0.60 to 0.60 / 0.40, or 0.45 / 0.55 to 0.55 / 0.45 from the viewpoint of curability. When the equivalent ratio is 0.30 / 0.70 or more, more sufficient curability tends to be obtained. When the equivalent ratio is 0.70 / 0.30 or less, it is possible to prevent the viscosity from becoming too high, and more sufficient fluidity can be obtained.
[0029] The total content of the (A) and (B) components may be 5 to 50 parts by mass, 10 to 40 parts by mass, or 15 to 30 parts by mass, based on 100 parts by mass of the total mass of the (A), (B), (C), and (D) components. When the total content of the (A) and (B) components is 5 parts by mass or more, the elastic modulus tends to be improved by crosslinking. When the total content of the (A) and (B) components is 50 parts by mass or less, the film handleability tends to be maintained.
[0030] (C) Component: Acrylic rubber The (C) component is a rubber having a structural unit derived from a (meth)acrylic acid ester as a main component. The content of the structural unit derived from a (meth)acrylic acid ester in the (C) component may be, for example, 70% by mass or more, 80% by mass or more, or 90% by mass or more based on the total amount of structural units. The (C) component may contain a structural unit derived from a (meth)acrylic acid ester having a crosslinkable functional group such as an epoxy group, an alcoholic or phenolic hydroxyl group, or a carboxyl group. The (C) component may contain a structural unit derived from acrylonitrile within a range satisfying the condition of the formula (1) described later, but the (C) component may not contain a structural unit derived from acrylonitrile because it is possible to further suppress the copper ion permeation in the adhesive and has better embeddability.
[0031] In the infrared absorption spectrum of component (C), the height of the absorption peak due to the stretching vibration of the carbonyl group is defined as P CO , the height of the peak due to the stretching vibration of the nitrile group is P CN Then, P CO and P CN may satisfy the condition of the following formula (1). P CN / P CO <0.070 (1)
[0032] Here, the carbonyl group is mainly derived from the (meth)acrylic acid ester structural unit, and the nitrile group is mainly derived from the acrylonitrile structural unit. The height of the absorption peak derived from the stretching vibration of the carbonyl group (P CO ) and the height of the peak due to the stretching vibration of the nitrile group (P CN ) have the meanings defined in the Examples.
[0033] P CN / P CO A small value of means that the component (C) contains few structural units derived from acrylonitrile. Therefore, a component (C) that does not contain any structural units derived from acrylonitrile can theoretically satisfy the condition of formula (1).
[0034] P CN / P CO is less than 0.070, and may be 0.065 or less, 0.060 or less, 0.055 or less, 0.050 or less, 0.040 or less, 0.030 or less, 0.020 or less, or 0.010 or less. CN / P CO When P is less than 0.070, it is possible to sufficiently suppress the permeation of copper ions into the adhesive. CN / P CO The smaller the value of P, the more effectively the copper ion permeation in the adhesive can be suppressed. CN / P CO As the value of is smaller, the cohesive strength of component (C) is reduced, and therefore embeddability also tends to be improved.
[0035] The glass transition temperature (Tg) of the (C) component may be -50 to 50°C or -30 to 30°C. When the (C) component has a Tg of -50°C or higher, the flexibility of the adhesive tends to be prevented from becoming too high. This makes it easier to cut the film-like adhesive during wafer dicing, and prevents the occurrence of burrs. When the (C) component has a Tg of 50°C or lower, the flexibility of the adhesive tends to be suppressed from decreasing. This makes it easier to fill voids sufficiently when the film-like adhesive is attached to a wafer. In addition, it is possible to prevent chipping during dicing due to a decrease in wafer adhesion. Here, the glass transition temperature (Tg) refers to a value measured using a DSC (differential scanning calorimeter) (for example, Thermo Plus 2, manufactured by Rigaku Corporation).
[0036] The weight average molecular weight (Mw) of component (C) may be 100,000 to 3,000,000 or 200,000 to 2,000,000. When Mw of component (C) is within such range, film formability, film strength, flexibility, tackiness, etc. can be appropriately controlled, and reflowability and embeddability can be improved. Here, Mw refers to a value measured by gel permeation chromatography (GPC) and converted using a calibration curve based on standard polystyrene.
[0037] Examples of commercially available products of component (C) include SG-70L, SG-P3, SG-708-6, WS-023 EK30, and SG-280 EK23 (all manufactured by Nagase ChemteX Corporation). Examples of commercially available products of component (C) that do not contain a structural unit derived from acrylonitrile include KH-CT-865 (manufactured by Hitachi Chemical Co., Ltd.).
[0038] The content of component (C) may be 50 to 95 parts by mass, 55 to 90 parts by mass, or 60 to 85 parts by mass, based on 100 parts by mass of the total mass of components (A), (B), (C), and (D). When the content of component (C) is within such a range, copper ion permeation within the adhesive tends to be more sufficiently suppressed.
[0039] (D) Component: Inorganic filler Examples of the (D) component include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, boron nitride, silica, etc. These may be used alone or in combination of two or more. Among these, the (D) component may be silica from the viewpoint of adjusting the melt viscosity.
[0040] From the viewpoint of flowability, the average particle size of component (D) may be 0.01 to 1 μm, 0.01 to 0.8 μm, or 0.03 to 0.5 μm. Here, the average particle size means a value calculated from the BET specific surface area. As the average particle size of component (D) becomes smaller, the appearance of the coating surface tends to be improved and the thin film coatability tends to be improved.
[0041] The shape of component (D) is not particularly limited, but may be spherical.
[0042] The content of the (D) component is 0.5 to 10 parts by mass relative to 100 parts by mass of the total mass of the (A), (B), (C) and (D) components. When the content of the (D) component is 0.5 parts by mass or more, the adhesive strength, wafer adhesion, elastic modulus and bulk strength of the film-like adhesive tend to be excellent. When the content of the (D) component is 10 parts by mass or less, the copper ion permeation in the adhesive is sufficiently suppressed, and the appearance and embeddability of the coated surface tend to be excellent. The content of the (D) component may be 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more, and may be 10 parts by mass or less, 9 parts by mass or less, 8.5 parts by mass or less, or 8 parts by mass or less.
[0043] The film-like adhesive (adhesive composition) may further contain a (E) coupling agent, a (F) curing accelerator, and the like.
[0044] Component (E): Coupling agent The component (E) may be a silane coupling agent. Examples of the silane coupling agent include γ-ureidopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-phenylaminopropyltrimethoxysilane, and 3-(2-aminoethyl)aminopropyltrimethoxysilane. These may be used alone or in combination of two or more.
[0045] (F) Component: Curing accelerator The (F) component is not particularly limited, and generally used ones can be used. Examples of the (F) component include imidazoles and their derivatives, organic phosphorus compounds, secondary amines, tertiary amines, and quaternary ammonium salts. These may be used alone or in combination of two or more. Among these, the (F) component may be imidazoles and their derivatives from the viewpoint of reactivity.
[0046] Examples of imidazoles include 2-methylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, etc. These may be used alone or in combination of two or more.
[0047] The film-like adhesive (adhesive composition) may further contain other components, such as pigments, ion scavengers, and antioxidants.
[0048] The contents of the components (E), (F) and other components may be 0 to 30 parts by mass per 100 parts by mass of the total of the components (A), (B), (C) and (D).
[0049] FIG. 1 is a schematic cross-sectional view showing one embodiment of a film-like adhesive. The film-like adhesive 1 (adhesive film) shown in FIG. 1 is obtained by forming an adhesive composition into a film. The film-like adhesive 1 may be in a semi-cured (B stage) state. Such a film-like adhesive 1 can be formed by applying the adhesive composition to a support film. When using a varnish of the adhesive composition (adhesive varnish), the (A) component, the (B) component, the (C) component, the (D) component, and other components added as necessary are mixed in a solvent, the mixed liquid is mixed or kneaded to prepare an adhesive varnish, the adhesive varnish is applied to a support film, and the solvent is removed by heating and drying, thereby forming the film-like adhesive 1.
[0050] The support film is not particularly limited as long as it can withstand the above-mentioned heat drying, and may be, for example, a polyester film, a polypropylene film, a polyethylene terephthalate film, a polyimide film, a polyetherimide film, a polyether naphthalate film, a polymethylpentene film, etc. The support film may be a multi-layer film combining two or more types, and may have a surface treated with a silicone-based, silica-based, or other mold release agent. The thickness of the support film may be, for example, 10 to 200 μm or 20 to 170 μm.
[0051] The mixing or kneading can be carried out using a conventional dispersing machine such as a stirrer, a grinding machine, a three-roll mill, or a ball mill, in appropriate combination.
[0052] The solvent used in preparing the adhesive varnish is not limited as long as it can dissolve, knead or disperse each component uniformly, and conventionally known solvents can be used. Examples of such solvents include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, toluene, and xylene. The solvent may be methyl ethyl ketone, cyclohexanone, etc., in terms of drying speed and price.
[0053] The adhesive varnish can be applied to the support film by a known method, such as knife coating, roll coating, spray coating, gravure coating, bar coating, curtain coating, etc. The conditions for heat drying are not particularly limited as long as the solvent used is sufficiently evaporated, and can be performed by heating at 50 to 150° C. for 1 to 30 minutes.
[0054] If the thickness of the film-like adhesive is 15 μm or less, the distance between the semiconductor element and the support member on which the semiconductor element is mounted becomes short, and therefore defects due to copper ions tend to occur easily. Since the film-like adhesive according to this embodiment can sufficiently suppress the permeation of copper ions in the adhesive, it is possible to make the thickness 15 μm or less. The thickness of the film-like adhesive 1 may be 12 μm or less or 10 μm or less. The lower limit of the thickness of the film-like adhesive 1 is not particularly limited, but can be, for example, 1 μm or more.
[0055] In one embodiment, the copper ion permeation time of the film-like adhesive 1 in the semi-cured (B stage) state may be more than 260 minutes, and may be 270 minutes or more, 280 minutes or more, 290 minutes or more, or 300 minutes or more. In other embodiments, the copper ion permeation time of the film-like adhesive 1 in the semi-cured (B stage) state may be more than 70 minutes, 75 minutes or more, or 80 minutes or more. By having the copper ion permeation time in such a range, it is expected that even if defects such as insufficient curing occur during the production of a semiconductor device, defects caused by copper ions will be less likely to occur.
[0056] In one embodiment, the adhesive strength (die shear strength) of the film-like adhesive 1 in the C-stage state (i.e., the cured product of the film-like adhesive) may be greater than 0.5 MPa, or may be 0.8 MPa or more, or 1.0 MPa or more. In other embodiments, the adhesive strength (die shear strength) of the film-like adhesive in the C-stage state may be greater than 1.5 MPa, or may be 1.6 MPa or more, 1.7 MPa or more, or 1.8 MPa or more. When the adhesive strength is within this range, defects due to peeling are unlikely to occur during the manufacture of the semiconductor manufacturing equipment, and it is predicted that the higher the adhesive strength, the lower the probability of defects due to peeling occurring.
[0057] Fig. 2 is a schematic cross-sectional view showing one embodiment of an adhesive sheet. Adhesive sheet 100 shown in Fig. 2 comprises a substrate 2 and a film-like adhesive 1 provided on the substrate 2. Fig. 3 is a schematic cross-sectional view showing another embodiment of an adhesive sheet. Adhesive sheet 110 shown in Fig. 3 comprises a substrate 2, a film-like adhesive 1 provided on the substrate 2, and a cover film 3 provided on the surface of the film-like adhesive 1 opposite to the substrate 2.
[0058] The substrate 2 is not particularly limited, but may be a substrate film. The substrate film may be the same as the above-mentioned support film.
[0059] The cover film 3 is used to prevent damage or contamination of the film-like adhesive, and may be, for example, a polyethylene film, a polypropylene film, a film with a surface treated with a release agent, etc. The thickness of the cover film 3 may be, for example, 15 to 200 μm or 70 to 170 μm.
[0060] The adhesive sheets 100 and 110 can be formed by applying an adhesive composition to a substrate film in the same manner as the method for forming the film-like adhesive described above. The method for applying the adhesive composition to the substrate 2 may be the same as the method for applying the adhesive composition to the support film described above.
[0061] The adhesive sheet 110 can be obtained by further laminating a cover film 3 onto the film-like adhesive 1 .
[0062] The adhesive sheets 100, 110 may be formed using a film-like adhesive prepared in advance. In this case, the adhesive sheet 100 can be formed by laminating under predetermined conditions (for example, at room temperature (20°C) or in a heated state) using a roll laminator, vacuum laminator, or the like. The adhesive sheet 100 may be formed in a heated state using a roll laminator, since this can be produced continuously and is highly efficient.
[0063] Another embodiment of the adhesive sheet is a dicing / die bonding integrated adhesive sheet in which the substrate 2 is a dicing tape. When a dicing / die bonding integrated adhesive sheet is used, the lamination process to the semiconductor wafer is performed only once, which makes it possible to improve the efficiency of the work.
[0064] Examples of the dicing tape include plastic films such as polytetrafluoroethylene film, polyethylene terephthalate film, polyethylene film, polypropylene film, polymethylpentene film, and polyimide film. The dicing tape may be subjected to surface treatment such as primer coating, UV treatment, corona discharge treatment, polishing treatment, and etching treatment, as necessary. The dicing tape may be adhesive. Such a dicing tape may be the above-mentioned plastic film to which adhesiveness has been imparted, or may be the above-mentioned plastic film to which an adhesive layer has been provided on one side. The adhesive layer may be either a pressure-sensitive type or a radiation-curing type, and is not particularly limited as long as it has sufficient adhesive strength to prevent the semiconductor element from scattering during dicing, and has low adhesive strength to the extent that the semiconductor element is not damaged in the subsequent semiconductor element pick-up process, and a conventionally known adhesive layer can be used.
[0065] The thickness of the dicing tape may be 60 to 150 μm or 70 to 130 μm from the viewpoints of economy and ease of handling of the film.
[0066] Examples of such dicing / die bonding integrated adhesive sheets include those having the configuration shown in FIG. 4 and those having the configuration shown in FIG. 5. FIG. 4 is a schematic cross-sectional view showing another embodiment of the adhesive sheet. FIG. 5 is a schematic cross-sectional view showing another embodiment of the adhesive sheet. An adhesive sheet 120 shown in FIG. 4 includes a dicing tape 7, a pressure-sensitive adhesive layer 6, and a film-like adhesive 1 in this order. An adhesive sheet 130 shown in FIG. 5 includes a dicing tape 7 and a film-like adhesive 1 provided on the dicing tape 7.
[0067] The adhesive sheet 120 can be obtained, for example, by providing a pressure-sensitive adhesive layer 6 on a dicing tape 7, and further laminating a film-like adhesive 1 on the pressure-sensitive adhesive layer 6. The adhesive sheet 130 can be obtained, for example, by bonding the dicing tape 7 and the film-like adhesive 1 together.
[0068] The film-like adhesive and adhesive sheet may be used in the manufacture of a semiconductor device, which may include a process of laminating a film-like adhesive and a dicing tape to a semiconductor wafer or an already diced semiconductor element (semiconductor chip) at 0°C to 90°C, then cutting with a rotary blade, laser or by stretching to obtain a semiconductor element with the film-like adhesive, and then adhering the semiconductor element with the film-like adhesive onto an organic substrate, a lead frame, or another semiconductor element.
[0069] Examples of semiconductor wafers include single crystal silicon, polycrystalline silicon, various ceramics, and compound semiconductors such as gallium arsenide.
[0070] The film-like adhesive and adhesive sheet can be used as a die-bonding adhesive for bonding semiconductor elements such as ICs and LSIs to lead frames such as 42 alloy lead frames and copper lead frames; plastic films such as polyimide resin and epoxy resin; substrates such as glass nonwoven fabrics impregnated and cured with plastics such as polyimide resin and epoxy resin; and support members for mounting semiconductors such as ceramics such as alumina.
[0071] The film-like adhesive and adhesive sheet are also suitably used as an adhesive for bonding semiconductor elements together in a stacked-PKG having a structure in which multiple semiconductor elements are stacked together, in which one of the semiconductor elements serves as a support member on which the semiconductor element is mounted.
[0072] The film-like adhesive and adhesive sheet can also be used, for example, as a protective sheet for protecting the back surface of a semiconductor element of a flip-chip type semiconductor device, or a sealing sheet for sealing the gap between the front surface of a semiconductor element of a flip-chip type semiconductor device and an adherend.
[0073] A semiconductor device manufactured using the film-like adhesive will be specifically described with reference to the drawings. Note that in recent years, semiconductor devices with various structures have been proposed, and the use of the film-like adhesive according to this embodiment is not limited to the semiconductor device with the structure described below.
[0074] Fig. 6 is a schematic cross-sectional view showing one embodiment of a semiconductor device. The semiconductor device 200 shown in Fig. 6 includes a semiconductor element 9, a support member 10 on which the semiconductor element 9 is mounted, and an adhesive member (cured film-like adhesive 1c) provided between the semiconductor element 9 and the support member 10 and bonding the semiconductor element 9 and the support member 10. A connection terminal (not shown) of the semiconductor element 9 is electrically connected to an external connection terminal (not shown) via a wire 11, and is sealed with a sealant 12.
[0075] 7 is a schematic cross-sectional view showing another embodiment of a semiconductor device. In a semiconductor device 210 shown in FIG. 7, a first-stage semiconductor element 9a is adhered to a support member 10 on which terminals 13 are formed by an adhesive member (cured film-like adhesive 1c), and a second-stage semiconductor element 9b is adhered to the first-stage semiconductor element 9a by an adhesive member (cured film-like adhesive 1c). The connection terminals (not shown) of the first-stage semiconductor element 9a and the second-stage semiconductor element 9b are electrically connected to external connection terminals via wires 11 and sealed by a sealant 12. In this way, the film-like adhesive according to this embodiment can be suitably used in a semiconductor device having a structure in which multiple semiconductor elements are stacked.
[0076] The semiconductor device (semiconductor package) shown in Figures 6 and 7 can be obtained, for example, by interposing a film-like adhesive between a semiconductor element and a support member or between two semiconductor elements, bonding them together by heating and pressing, and then, as necessary, going through a wire bonding process, a sealing process using a sealing material, a heat melting process including solder reflow, etc. In the heat and pressure bonding process, the heating temperature is usually 20 to 250°C, the load is usually 0.1 to 200 N, and the heating time is usually 0.1 to 300 seconds.
[0077] As a method for interposing a film-like adhesive between a semiconductor element and a support member or between semiconductor elements, as described above, a semiconductor element with a film-like adhesive may be prepared in advance and then attached to the support member or the semiconductor element.
[0078] The support member may include a member made of copper. In the semiconductor device according to the present embodiment, the semiconductor element and the support member are bonded by the cured product 1c of the film-like adhesive, so that even if a member made of copper is used as a component of the semiconductor device, the influence of copper ions generated from the member can be reduced, and the occurrence of electrical defects caused by copper ions can be sufficiently suppressed.
[0079] Here, examples of components made of copper include lead frames, wiring, wires, heat dissipation materials, etc., and when copper is used for any component, it is possible to reduce the effects of copper ions.
[0080] Next, a description will be given of one embodiment of a method for manufacturing a semiconductor device when using a dicing / die bonding integrated adhesive sheet shown in Fig. 4. Note that the method for manufacturing a semiconductor device using a dicing / die bonding integrated adhesive sheet is not limited to the method for manufacturing a semiconductor device described below.
[0081] First, a semiconductor wafer is pressure-bonded to the film-like adhesive 1 in the adhesive sheet 120 (dicing / die bonding integrated adhesive sheet), and the semiconductor wafer is adhered and fixed (mounting process). This process may be performed while pressing with a pressing means such as a pressing roll.
[0082] Next, the semiconductor wafer is diced. This cuts the semiconductor wafer to a predetermined size to produce a plurality of individual semiconductor elements (semiconductor chips) with a film-like adhesive. Dicing can be performed, for example, from the circuit surface side of the semiconductor wafer according to a conventional method. In this process, for example, a cutting method called full cut in which cutting is performed up to the dicing tape, a method in which a half cut is made in the semiconductor wafer and then divided by cooling and pulling, a cutting method using a laser, etc. can be used. The dicing device used in this process is not particularly limited, and a conventionally known device can be used.
[0083] In order to peel off the semiconductor element bonded to the dicing / die bonding integrated adhesive sheet, the semiconductor element is picked up. The pick-up method is not particularly limited, and various conventionally known methods can be used. For example, there is a method in which each semiconductor element is pushed up from the dicing / die bonding integrated adhesive sheet side by a needle, and the pushed-up semiconductor element is picked up by a pick-up device.
[0084] Here, when the adhesive layer is a radiation (e.g., ultraviolet) curable type, the pick-up is performed after irradiating the adhesive layer with radiation. This reduces the adhesive strength of the adhesive layer to the film-like adhesive, making it easier to peel off the semiconductor element. As a result, the semiconductor element can be picked up without being damaged.
[0085] Next, the semiconductor element with the film-like adhesive formed by dicing is bonded to a support member for mounting the semiconductor element via the film-like adhesive. The bonding may be performed by pressure bonding. The die bonding conditions are not particularly limited and can be set appropriately as necessary. Specifically, for example, the die bonding temperature can be set within the range of 80 to 160°C, the bonding load 5 to 15N, and the bonding time 1 to 10 seconds.
[0086] If necessary, a step of thermally curing the film-like adhesive may be provided. By thermally curing the film-like adhesive that bonds the support member and the semiconductor element in the above-mentioned bonding step, it is possible to bond and fix more firmly. When performing thermal curing, pressure may be applied at the same time to harden the adhesive. The heating temperature in this step can be appropriately changed depending on the components of the film-like adhesive. The heating temperature may be, for example, 60 to 200°C. The temperature or pressure may be changed stepwise.
[0087] Next, a wire bonding process is performed in which the tip of the terminal portion (inner lead) of the support member is electrically connected to the electrode pad on the semiconductor element by a bonding wire. For example, a gold wire, an aluminum wire, a copper wire, etc. are used as the bonding wire. The temperature during wire bonding may be within a range of 80 to 250°C or 80 to 220°C. The heating time may be several seconds to several minutes. Wire bonding may be performed by combining ultrasonic vibration energy and compression energy by applied pressure in a heated state within the above temperature range.
[0088] Next, an encapsulation process is performed to encapsulate the semiconductor element with an encapsulation resin. This process is performed to protect the semiconductor element or the bonding wires mounted on the support member. This process is performed by molding the encapsulation resin in a mold. The encapsulation resin may be, for example, an epoxy-based resin. The substrate and residue are embedded by the heat and pressure during encapsulation, and peeling due to air bubbles at the adhesive interface can be prevented.
[0089] Next, in the post-curing step, the sealing resin that was not sufficiently cured in the sealing step is completely cured. Even if the film-like adhesive is not thermally cured in the sealing step, the film-like adhesive can be thermally cured in this step together with the curing of the sealing resin, thereby enabling adhesion and fixation. The heating temperature in this step can be appropriately set depending on the type of sealing resin, and may be, for example, within the range of 165 to 185°C, and the heating time may be about 0.5 to 8 hours.
[0090] Next, the semiconductor element with the film-like adhesive attached to the support member is heated using a reflow furnace. In this process, the resin-encapsulated semiconductor device may be surface-mounted on the support member. Examples of the surface mounting method include reflow soldering, in which solder is supplied in advance onto a printed wiring board, then heated and melted by hot air or the like, and soldered. Examples of the heating method include hot air reflow and infrared reflow. The heating method may be a method of heating the entire surface or a method of heating a local area. The heating temperature may be, for example, within a range of 240 to 280°C.
[0091] When semiconductor elements are laminated in multiple layers, the heat history during wire bonding and other processes increases, and the impact of air bubbles present at the interface between the film-like adhesive and the semiconductor elements on peeling can be significant. However, the film-like adhesive according to this embodiment tends to have a lower cohesive force and improved embeddability by using a specific acrylic rubber. Therefore, air bubbles are less likely to be trapped in the semiconductor device, and the air bubbles can be easily diffused during the sealing process, preventing peeling due to air bubbles at the adhesive interface. EXAMPLES
[0092] The present invention will be specifically described below based on examples, but the present invention is not limited to these.
[0093] [Preparation of film adhesive] Examples and Comparative Examples <Preparation of adhesive varnish> Cyclohexanone was added to a composition consisting of (A) epoxy resin as a thermosetting resin, (B) phenolic resin as a curing agent, and (D) inorganic filler, with the product names and composition ratios (unit: parts by mass) shown in Tables 1 and 2, and mixed by stirring. (C) acrylic rubber shown in Tables 1 and 2 was added to this and stirred, and (E) coupling agent and (F) curing accelerator shown in Tables 1 and 2 were further added and stirred until each component was uniform, to prepare an adhesive varnish. The numerical values of (C) component and (D) component shown in Tables 1 and 2 refer to parts by mass of solid content.
[0094] (A) Thermosetting resin (A1) YDCN-700-10 (trade name, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., o-cresol novolac type epoxy resin, epoxy equivalent: 209 g / eq)
[0095] (B) Hardener (B1) HE-100C-30 (trade name, manufactured by Air Water Inc., phenylaralkyl type phenolic resin, hydroxyl equivalent: 174 g / eq, softening point 77° C.)
[0096] (C) Acrylic rubber (C1) SG-P3 improved product (SG-P3 (trade name, manufactured by Nagase ChemteX Corporation) acrylic rubber with the structural unit derived from acrylonitrile removed; weight average molecular weight of acrylic rubber: 600,000; theoretical Tg of acrylic rubber: 12°C; P CN / P CO =0.001) (C2) SG-P3 solvent change product (SG-P3 (product name, Nagase Chemtex Corporation, acrylic rubber methyl ethyl ketone solution) solvent change product, acrylic rubber weight average molecular weight: 800,000, acrylic rubber theoretical Tg: 12°C, P CN / P CO =0.070)
[0097] (IR spectrum measurement) P of (C1) and (C2) CN / P CO was calculated by the following method. First, the solvent was removed from (C1) and (C2) and the transmission IR spectrum was measured by the KBr tablet method, and the vertical axis was the absorbance and the horizontal axis was the wave number (cm -1 The IR spectrum was measured using an FT-IR6300 (manufactured by JASCO Corporation, light source: high-intensity ceramic light source, detector: DLATGS).
[0098] (The height of the absorption peak due to the stretching vibration of the carbonyl group P CO ) 1670cm -1 and 1860cm -1 The peak with the highest absorbance between these two points was taken as the peak point. -1 and 1860cm -1 The straight line between these two points is taken as the baseline, and the point on this baseline that is the same wavenumber as the peak point is taken as the baseline point. The difference in absorbance between the baseline and the peak point is taken as the height of the absorption peak resulting from the stretching vibration of the carbonyl group (P CO ) was decided.
[0099] (The height of the peak due to the stretching vibration of the nitrile group P CN ) P CO In the same IR spectrum as that used to calculate -1 and 2220cm -1 The peak with the highest absorbance between these two points was taken as the peak point. -1 and 2220cm -1The straight line between these two points is taken as the baseline, and the point on this baseline that is the same wavenumber as the peak point is taken as the baseline point. The difference in absorbance between the baseline and the peak point is taken as the height of the peak due to the stretching vibration of the nitrile group (P CN ) was decided.
[0100] (D) Inorganic filler (D1) SC2050-HLG (product name, manufactured by Admatechs Co., Ltd., silica filler dispersion, average particle size 0.50 μm)
[0101] (E) Coupling Agent (E1) A-189 (trade name, manufactured by Nippon Unicar Co., Ltd., γ-mercaptopropyltrimethoxysilane) (E2) A-1160 (trade name, manufactured by Nippon Unicar Co., Ltd., γ-ureidopropyltriethoxysilane)
[0102] (F) Curing accelerator (F1) 2PZ-CN (trade name, manufactured by Shikoku Chemical Industry Co., Ltd., 1-cyanoethyl-2-phenylimidazole)
[0103] <Preparation of film adhesive> The prepared adhesive varnish was filtered through a 100 mesh filter and vacuum degassed. A polyethylene terephthalate (PET) film with a thickness of 38 μm that had been subjected to a release treatment was prepared as a substrate film, and the adhesive varnish after vacuum degassing was applied onto the PET film. The applied adhesive varnish was heated and dried in two stages at 90° C. for 5 minutes and then at 130° C. for 5 minutes to obtain film-like adhesives in a B-stage state of Examples 1-1 and 1-2, Comparative Examples 1-1 and 1-2, Examples 2-1 and 2-2, and Comparative Examples 2-1 and 2-2. The thickness of the film-like adhesive was adjusted to 10 μm depending on the amount of adhesive varnish applied.
[0104] [Table 1]
[0105] [Table 2]
[0106] [Measurement of Copper Ion Permeation Time] [Preparation of Solution A] 2.0 g of anhydrous copper(II) sulfate was dissolved in 1020 g of distilled water, and the solution was stirred until the copper sulfate was completely dissolved to prepare an aqueous copper sulfate solution with a copper ion concentration of 500 mg / kg in terms of Cu element. The obtained aqueous copper sulfate solution was designated as Solution A.
[0107] [Preparation of Solution B] 1.0 g of anhydrous sodium sulfate was dissolved in 1000 g of distilled water, and the solution was stirred until the sodium sulfate was completely dissolved. Then, 1000 g of N-methyl-2-pyrrolidone (NMP) was added thereto and stirred. Thereafter, the solution was air-cooled to room temperature to obtain an aqueous sodium sulfate solution. The obtained solution was designated as Solution B.
[0108] [Measurement of Copper Ion Permeation Time] The film adhesives (thickness: 10 μm) of Example 1-1, 1-2 and Comparative Example 1-2 and Example 2-1, 2-2 and Comparative Example 2-2 prepared above were each cut out into a circular shape with a diameter of about 3 cm. Next, two silicon packing sheets with a thickness of 1.5 mm, an outer diameter of about 3 cm and an inner diameter of 1.8 cm were prepared. The film adhesives cut out into a circular shape were sandwiched between the two silicon packing sheets, and this was sandwiched between the flange portions of two glass cells with a volume of 50 mL and fixed with a rubber band.
[0109] Next, 50 g of solution A was poured into one glass cell, and then 50 g of solution B was poured into the other glass cell. Mars Carbon (Staedtler LLC, φ2mm / 130mm) was inserted as a carbon electrode into each cell. The anode was connected to a DC power source (A&D Co., Ltd., DC power supply AD-9723D) with the solution A side as the anode and the solution B side as the cathode. The cathode and the DC power source were connected in series via an ammeter (Sanwa Electric Instruments Co., Ltd., Digital multimeter PC-720M). A voltage of 24.0V was applied at room temperature, and measurement of the current value was started after the application. The measurement was continued until the current value exceeded 15μA, and the time when the current value reached 10μA was defined as the copper ion permeation time. The results are shown in Tables 3 and 4. In this evaluation, it can be said that the longer the permeation time, the more the copper ion permeation is suppressed.
[0110] [Appearance evaluation of coated surface] The appearance of the coated surface of the film-like adhesives of Examples 1-1 and 1-2, Comparative Example 1-2, and Examples 2-1, 2-2, and Comparative Example 2-2 was evaluated by visual inspection to check for the presence of foreign matter, voids, streaks, etc. Those for which no foreign matter, voids, streaks, etc. were found were rated "A", those for which foreign matter, voids, streaks, etc. were found were rated "B", and those for which a large amount of foreign matter, voids, streaks, etc. were found were rated "C". The results are shown in Tables 3 and 4.
[0111] [Table 3]
[0112] [Table 4]
[0113] [Adhesive strength evaluation] <Fabrication of semiconductor device> A dicing tape (Hitachi Chemical Co., Ltd., thickness 110 μm) was prepared, and the film-like adhesives (thickness 10 μm) of Examples 1-1, 1-2, Comparative Example 1-1, and Examples 2-1, 2-2, and Comparative Example 2-1 were attached to prepare a dicing-die bonding integrated adhesive sheet having a dicing tape and a film-like adhesive. A 400 μm thick semiconductor wafer was laminated on the film-like adhesive side of the dicing-die bonding integrated adhesive sheet at a stage temperature of 70° C. to prepare a dicing sample.
[0114] The obtained diced sample was cut using a fully automatic dicer DFD-6361 (manufactured by Disco Corporation). Cutting was performed by a step-cut method using two blades, and dicing blades ZH05-SD3500-N1-xx-DD and ZH05-SD4000-N1-xx-BB (both manufactured by Disco Corporation) were used. The cutting conditions were a blade rotation speed of 4000 rpm, a cutting speed of 50 mm / sec, and a chip size of 7.5 mm x 7.5 mm. The first cutting step was performed so that about 30 μm of the semiconductor wafer remained, and then the second cutting step was performed so that about 20 μm of cut was made in the dicing tape.
[0115] Next, the semiconductor chip obtained by cutting was thermocompression bonded onto a solder resist (Taiyo Holdings Co., Ltd., product name: AUS-308). The bonding conditions were a temperature of 120°C, a time of 1 second, and a pressure of 0.1 MPa. Next, the sample obtained by bonding was placed in a dryer and cured at 170°C for 1 hour. The semiconductor chip bonded to the solder resist was cured, and the semiconductor chip was hooked and pulled with a universal bond tester (manufactured by Nordson Advanced Technology Co., Ltd., product name: Series 4000) to measure the die shear strength after curing between the semiconductor chip and the solder resist, and evaluated as the adhesive strength. The measurement conditions were a stage temperature of 250°C. The results are shown in Tables 5 and 6.
[0116] [Table 5]
[0117] [Table 6]
[0118] As shown in Tables 5 and 6, film-type adhesives having an inorganic filler content of 0.5 to 10 parts by mass per 100 parts by mass of the total mass of the thermosetting resin, curing agent, acrylic rubber, and inorganic filler had a longer copper ion permeation time and superior adhesive strength compared to film-type adhesives that did not meet this requirement.
[0119] As described above, it has been confirmed that the film-like adhesive of the present invention sufficiently suppresses copper ion permeation within the adhesive, while also exhibiting excellent adhesive strength. [Explanation of symbols]
[0120] Reference Signs List 1...film-like adhesive, 2...substrate, 3...cover film, 6...adhesive layer, 7...dicing tape, 9, 9a, 9b...semiconductor element, 10...support member, 11...wire, 12...sealant, 13...terminal, 100, 110, 120, 130...adhesive sheet, 200, 210...semiconductor device.
Claims
1. A support member; a first semiconductor element adhered onto the support member by a first adhesive member; a second semiconductor element bonded onto the first semiconductor element by a second adhesive member; A semiconductor device having a stacked semiconductor element structure, the first adhesive member and the second adhesive member are cured products of a film-like adhesive, the film-like adhesive contains a thermosetting resin, a curing agent, an acrylic rubber, and an inorganic filler; the content of the acrylic rubber is 60 to 85 parts by mass with respect to 100 parts by mass of the total mass of the thermosetting resin, the curing agent, the acrylic rubber, and the inorganic filler; the content of the inorganic filler is 0.5 to 10 parts by mass with respect to 100 parts by mass of the total mass of the thermosetting resin, the curing agent, the acrylic rubber, and the inorganic filler; The semiconductor device, wherein the thickness of the film-like adhesive is 15 μm or less.
2. The semiconductor device according to claim 1 , wherein the support member includes a member made of copper.
Citation Information
Patent Citations
Semiconductor element with film pasted, semiconductor device, and manufacturing method therefor
JP2004221555A
Adhesive sheet for manufacturing semiconductor device, semiconductor device containing adhesive sheet for manufacturing semiconductor device, and method of manufacturing semiconductor device
JP2013026566A
Adhesive film
JP2016190964A
Adhesive composition, filmy adhesive, adhesive sheet, and semiconductor device made with the same
WO2007083810A1